2015
DOI: 10.1007/s00424-015-1702-8
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Ca2+-induced Ca2+ release from intracellular stores contributes to catecholamine hypersecretion in adrenal chromaffin cells from spontaneously hypertensive rats

Abstract: Adrenal chromaffin cells (CCs) from spontaneously hypertensive rats (SHRs) secrete more catecholamine (CA) upon stimulation than CCs from normotensive Wistar Kyoto rats (WKY). Unitary CA exocytosis events, both spontaneous and stimulated, were amperometrically recorded from cultured WKY and SHR CCs. Both strains display spontaneous amperometric spikes but SHR CCs produce more spikes and of higher mean amplitude. After a brief stimulation with high K(+) or caffeine which produces voltage-gated Ca(2+) influx or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
19
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 77 publications
6
19
0
1
Order By: Relevance
“…Figures 1A and 1B are representative amperometric recordings obtained from a WKY and an SHR CC in response to depolarizing stimuli. As reported earlier, SHR CCs produced more secretory events than WKY CCs after each stimulation [34]. Also, the kinetic parameters of the amperometric spikes showed noticeable inter-strain differences (see Figs.…”
Section: Resultssupporting
confidence: 79%
See 3 more Smart Citations
“…Figures 1A and 1B are representative amperometric recordings obtained from a WKY and an SHR CC in response to depolarizing stimuli. As reported earlier, SHR CCs produced more secretory events than WKY CCs after each stimulation [34]. Also, the kinetic parameters of the amperometric spikes showed noticeable inter-strain differences (see Figs.…”
Section: Resultssupporting
confidence: 79%
“…In CCs with two Ca 2+ components, simultaneous amperometry also shows two bursts of exocytosis. The late Ca 2+ transient component is abolished with CPA and Ryanodine, suggesting that it represents the contribution of CICR.Previously, we reported that membrane depolarization triggered [Ca 2+ ]c elevations and catecholamine secretion ~ 3 fold greater in CCs from SHRs than age-matched WKY rats CCs[34], and that ryanodine, a RyRs blocker, caused a drastic reduction (77%) in amperometric cumulative charge, mainly due to a 71% decrease in the number of spikes[34], demonstrating that CICR contribution to catecholamine hypersecretion in SHR CCs is linked to stronger intracellular Ca 2+ signals. Possible explanations for the enhanced gain of CICR in SHR CCs include excessive RyRs expression, greater Ca 2+ content of the SER, and increased Ca 2+ sensitivity of the RyRs.Since ryanodine speci cally suppressed CA hypersecretion in SHR CCs, it could be hypothesized that agents that inhibit RyR function could attenuate hypertension development in this animal model.…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…The animal tail was placed in contact with a cuff, and a pulse transducer was used to measure the systolic blood pressure (SBP), diastolic blood pressure (DBP), heart rate (HR), and mean arterial pressure (MAP). An average of 4 pressure readings was recorded for each measurement [ 35 ].…”
Section: Methodsmentioning
confidence: 99%